- #1

johnhuntsman

- 76

- 0

I'd really like for someone to explain the last bit of the equation used in the Atwood's Machine experiment. [Forget this gray part]Specifically, I don't understand what F means in F = Mg - mg = (M - m)g, and would appreciate that being defined. Secondly, I don't understand why a = F/(M+m) is even part of the equation. I have a lab report due Monday and need help understanding this firstly.

The "master" equation in question, BTW, being a = [(M-m)g]/(M+m).

The "master" equation in question, BTW, being a = [(M-m)g]/(M+m).

Last edited: